Analytical description of lateral binding force exerted on bi-sphere induced by high-order Bessel beams. (July 2018) - Bai, J.; Wu, Z.S.; Ge, C.X.; Li, Z.J.; Qu, T.; Shang, Q.C.
Highlights: The lateral binding force exerted on bi-sphere induced by a high-order Bessel beam with arbitrary polarization angles is studied analytically. The accuracy of the theory and codes is verified. Numerical effects of various parameters and different properties are numerically analyzed in detail. Even more so in hindsight of these parameters with respect to optical binding clearly shows that in what case optical binding exists as a fine balance between those parameters. Abstract: Based on the generalized multi-particle Mie equation (GMM) and Electromagnetic Momentum (EM) theory, the lateral binding force (BF) exerted on bi-sphere induced by an arbitrary polarized high-order Bessel beam (HOBB) is investigated with particular emphasis on the half-conical angle of the wave number components and the order (or topological charge) of the beam. The illuminating HOBB with arbitrary polarization angle is described in terms of beam shape coefficients (BSCs) within the framework of generalized Lorenz-Mie theories (GLMT). Utilizing the vector addition theorem of the spherical vector wave functions (SVWFs), the interactive scattering coefficients are derived through the continuous boundary conditions on which the interaction of the bi-sphere is considered. Numerical effects of various parameters such as beam polarization angles, incident wavelengths, particle sizes, material losses and the refractive index, including the cases of weak, moderate, and strong than the surrounding medium are numerically analyzed in detail. The observed dependence of the separation of optically bound particles on the incidence of HOBB is in agreement with earlier theoretical prediction. Accurate investigation of BF induced by HOBB could provide an effective test for further research on BF between more complex particles, which plays an important role in using optical manipulation on particle self-assembly.